A Fuzzy Set Analysis of Foreign-Owned Subsidiary Performance: Insights from East Asia. Issue 4 (2nd October 2017) - Dahms, Sven
ABSTRACT: The purpose of this study is to investigate the multiple conditions that affect performance in foreign-owned subsidiaries. This research is based on a survey of foreign-owned subsidiaries located in the midrange emerging economy of Taiwan. The resulting data set consists of 226 subsidiary managers' responses. Using configurational theory to guide our argumentations, the author shows that three different paths lead to higher performance, hence, indicating equifinality. Overall, results show that only subsidiary competences are a core condition for high performance. Networks, autonomy, market orientation, industry, and relatedness are only peripheral.